Case report: A case of duodenal adenocarcinoma achieving significantly long survival treating with immune checkpoint inhibitors and chemotherapy without positive biomarkers - Chen, Xian; Zhou, Rui; Li, Yong; Qu, Xin; Qu, Yan-chun; Li, Wen-zhu; Ye, Yong-song; Liu, Li-rong; Zhu, Yan-juan; Zhang, Hai-bo (Frontiers in Immunology, 2022)
Small bowel adenocarcinoma (SBA), particularly duodenal adenocarcinoma (DA), is a rare gastrointestinal cancer with a dismal prognosis. Data on SBA treatments are limited, and the therapeutic strategy remains uncertain. Currently, chemotherapy is the most used treatment; however, it has a poor median progression-free survival (mPFS) of no more than five months in the second-line setting. We report a case with DA that responded well to the immune checkpoint inhibitor (ICI) tislelizumab plus irinotecan in the second-line treatment. To our knowledge, this is the first report of administering ICIs plus chemotherapy to SBA. Despite the absence of microsatellite instability-high (MSI-H) and high tumor mutational burden (TMB), the patient with TP53/KRAS mutation achieved a significantly long PFS of 17 months, and the benefit is still ongoing. The mechanism of this remarkable efficacy might be associated with an increase in tumor immunogenicity after chemotherapy. The current study presents a promising effect of ICIs plus chemotherapy on SBA, affirming the need to investigate the clinical value of this combination in SBA and the underlying mechanism behind it.